To solve for m we want to get m by itself on one side of the equals sign, with everything else on the other side. First we subtract b from both sides, to get it out of the right side of the equation:
y - b = mx + b - b
y - b = mx
Now we divide both sides by x, to get m completely by itself:
(y-b)/x = (mx)/x
(y-b)/x = m
So m is equal to (y-b)/x.
5 + 6a + 11b
terms: 5; 6a; 11b
Factors of 5: 1; 5
Factors of 6a: 1; 2; 3; 6; a; 2a; 3a; 6a
Factors of 11b: 1; 11; b; 11b
R=-4
desmos is a good app to check out these priblems (i do it all the time)
Answer:
(7×x)+14
Step-by-step explanation: Because we have 14 added to something, we will need a + to whatever we are adding to. The product of 7 and a number is 7×x because product is the number you get after multiplication. So we get 7×x+14. You dont need parenthesis
Hope this helps!
Answer:
7x^2 -5x + 4
Step-by-step explanation:
5x^2 – 6x+2
- (-2x^2 - x - 2)
We got 5x^2 - (-2x^2) = 5x^2 + 2x^2 = 7x^2
-6x - (-x) = -6x + x = -5x
2 - (-2) = 2+2 = 4
So the equation would be 7x^2 -5x + 4
Hope this help :3